PENDAMPINGAN TEKNIS PENDAFTARAN SPP-IRT DAN INOVASI LABEL KEMASAN UNTUK UMKM PRODUK KOPI GUNUNG WANGUN DUA - Novidahlia, Noli; Nurjanah, Eka Wulan; Ramadhan, Muhamad Fauzi; Susanto, Muhammad Fajry; Choironi, Nida; Indriyani, Resty; Febriani, Rindiana; Gusrani, Salsabila Syifa; Zakiyyah, Syahla (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
Gunung Wangun Dua Coffee is a typical Bogor coffee that has a delicious taste and achievements in national and international competitions. Production and marketing of this coffee is carried out by MSME Gunung Wangun Dua. Marketing of this coffee is very limited because it does not yet have a Home Industry Food Product Certificate (SPP-IRT) as a Distribution Permit. Registration of this distribution permit requires complete business and production documents as well as good facilities. UMKM Gunung Wangun Dua accompanied by Thematic Real Work (KKN-T) students from Juanda University, Bogor, is trying to obtain the distribution permit by completing business documents and production documents consisting of Product Information List documents, Production Records, SOPs for Including Packaging Labels and SOPs for Selection. materials and design packaging labels that are good and correct according to BPOM regulations. The SPP-IRT registration process on the One Single Submission (OSS-RBA) system is accompanied directly by KKN-T students until the Distribution Permit becomes effective. The distribution permit number for Gunung Wangun Dua coffee products is PIRT: 290523001106600000001 Keywords: Coffee, SPP-IRT, Document, Packaging, Label